Adiponectin is not associated with renal function decline in community-dwelling elderly adults. Issue 21 (May 2018) - Kobayashi, Hiroki; Otsuka, Hiromasa; Yanai, Mitsuru; Haketa, Akira; Hara, Motohiko; Hishiki, Mikano; Abe, Masanori; Soma, Masayoshi
Abstract : Abstract: Adiponectin secreted by adipocytes plays an important role in the regulation of glucose and fatty acid metabolism. Contrary to findings in patients with chronic kidney disease (CKD), no prospective data about the association of serum adiponectin with renal function decline in the general population have yet appeared. Our objective was to analyze the relationship of total and high molecular weight (HMW) adiponectin with renal function decline as measured by cystatin C in community-dwelling elderly adults without moderate or severe CKD. In a prospective observational analysis, a total of 216 healthy elderly volunteers with eGFRcys ≥60 mL/min/1.73 m 2 underwent anthropometric and laboratory tests at baseline and at follow-up visits. A subgroup with serum samples collected 5 years apart was further analyzed. There were no differences in either total or HMW adiponectin level between subjects subsequently undergoing rapid renal function decline and subjects with normal physiologic renal function decline ( P = .71, P = .81). On univariate linear regression, neither total nor HMW adiponectin were associated with annual renal function decline (β = −0.23; P = .71, β = −0.057; P = .90). Multivariate analysis did not show a significant contribution of either total or HMW adiponectin to annual renal function decline (β = −0.50; P = .46, β = 0.01; P = .98). In the logistic regression analysis, we did not observe any statistically significant association of serum adiponectin levels with rapid renal function decline or incidence of CKD. Contrary to findings in populations with CKD, neither total nor HMW adiponectin had a substantial association with renal function decline in an elderly population with eGFRcys ≥60 mL/min/1.73 m 2 . Our results and conclusions should not be extrapolated to subjects with other characteristics.